"I'm doing this test so I can benefit from PrEP": exploring HIV testing barriers/facilitators and implementation of pre-exposure prophylaxis among South African adolescents. Issue 2 (2nd April 2020) - Yoshioka, Emily; Giovenco, Danielle; Kuo, Caroline; Underhill, Kristen; Hoare, Jackie; Operario, Don
Abstract : In South Africa, adolescents are a key population in the HIV epidemic that can benefit from increased access to oral pre-exposure prophylaxis (PrEP). HIV testing is an integral component of the PrEP care continuum but adolescents in South Africa have generally low HIV testing rates; therefore, adolescents' HIV testing attitudes and behaviours must be understood to develop strategies for effective PrEP implementation. Ten focus groups were conducted with adolescents living with HIV and HIV-uninfected adolescents ( n = 55), and in-depth interviews were conducted with service providers ( n = 25), adolescents living with HIV ( n = 10) and HIV-uninfected adolescents ( n = 25). Data were collected in the Western Cape province of South Africa from 2015–2016. Thematic framework analysis was used to understand dynamics by which South African adolescents' attitudes toward HIV testing might influence intended uptake of PrEP and, reciprocally, to explore the implications of adolescents' perceptions about PrEP availability for their willingness to engage in HIV testing. While South African adolescents' current HIV testing attitudes and behaviours present barriers to intended PrEP implementation in this population, increased access to PrEP has the potential to improve their initial HIV testing rates and decrease stigma and fear around HIV testing. However, implementation of PrEP must consider specific HIV testing barriers for adolescent boys and girls, respectively. As PrEP becomes more widely available for adolescents, possible challenges noted by participants may include the potential for adolescents to reduce continued HIV testing behaviours while on PrEP and to share/use unprescribed PrEP medications among peers.